Diseño e implementación de un banco didáctico de pruebas para la programación de PLC Schneider electric. (2020)
In the exercise within the professional field, electromechanical engineers must face challenges of constant automation in the different processes of production of goods and services, with the development of this degree work it is sought that the students of the University's electromechanical engineering program Antonio Nariño Villavicencio headquarters can reinforce the knowledge acquired in the classes and put it into practice on time in subjects related to industrial electronics and programming. As a consequence of the above, a didactic test bench for PLC programming is designed and implemented, where it initially starts from a study of preliminary concepts for the selection of the elements, then its design, its manufacture and finally its tests. operating.